The Fifth United Arab Emirates Obesity Conference, November 4–5, 2023, Abu Dhabi, UAE - Bondugulapati, L. N. Rao; Nawar, Rita; Abusahmin, Hussam; Ghazanfar, Rahat; Beshyah, Salem A. (Journal of Diabetes and Endocrine Practice, 2023)
The Fifth United Arab Emirates Obesity Conference was held from November 4 to 5, 2023, in Dusit Thani, Abu Dhabi, UAE. The theme of the conference was “What can we do better in obesity management?” The program included several didactic lectures and a question-and-answer time separately or grouped thematically. Over 2 days, the speakers covered the burden, definitions, and evaluation of obesity, including uncommon chromosomal and genetic syndromes associated with obesity in appropriate cases. It highlighted the importance of policy changes for public health improvement and prevention of obesity, the role of multidisciplinary teams in managing persons with obesity holistically, and present and future therapies, including personalized precision medicine backed up by science.
Keywords: overweight; obesity; morbid obesity; bariatric surgery; management; prevention